2018
DOI: 10.1007/s10552-018-1069-1
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional nativity and racial/ethnic disparities in human papillomavirus vaccination initiation among U.S. women: a national population-based study

Abstract: We observed pronounced HPV vaccination initiation disparities among foreign-born women in relation to race/ethnicity and between foreign-born women from minoritized racial/ethnic backgrounds and U.S.-born white women. Research on nativity disparities in HPV vaccination should take into account race/ethnicity, and vice versa. Interventions that seek to facilitate HPV vaccination among foreign-born women are needed and should address the unique needs of those from minoritized racial/ethnic backgrounds to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Indeed, our findings suggest low coverage of HPV vaccination among foreign-born women and men. Similar to other studies showing lower rates of HPV vaccine initiation among foreign-born than among U.S.-born populations in those 20 to 25 years old (10% vs. 20%), 8,9 we found that fewer than 1 in 10 foreign-born adults ages 35 and younger had received any doses of the vaccine. If left unaddressed, disparities in utilization of these health services will likely lead to continued HPV-related cancer disparities in the long term.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, our findings suggest low coverage of HPV vaccination among foreign-born women and men. Similar to other studies showing lower rates of HPV vaccine initiation among foreign-born than among U.S.-born populations in those 20 to 25 years old (10% vs. 20%), 8,9 we found that fewer than 1 in 10 foreign-born adults ages 35 and younger had received any doses of the vaccine. If left unaddressed, disparities in utilization of these health services will likely lead to continued HPV-related cancer disparities in the long term.…”
Section: Discussionsupporting
confidence: 90%
“…First, the lower prevalence of HPV among men and women who were foreign-born indicates that disparities related to HPV and nativity, such as higher levels of cervical cancer mortality among foreign-born women, are not likely due to higher rates of infection or high-risk infection. Rather, other known disparities, such as lower vaccination, lower screening participation, delayed diagnosis, and poorer access to care, [8][9][10][11][12][13] may explain the discrepancy between this population's lower prevalence of HPV infection but increased risk of negative HPV-related outcomes. Indeed, our findings suggest low coverage of HPV vaccination among foreign-born women and men.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Example 2: Human Papillomavirus (HPV) Vaccination HPV vaccination is an effective method of preventing cervical cancer in women. However, compared with other foreign-born women of color, foreign-born Asian women have the lowest adjusted odds of HPV vaccine initiation compared with U.S.-born NHWs (odds ratio, OR = 0.26; Agénor et al, 2018). This disparity is of special concern for East Asians because .76% of Chinese and Koreans in the United States are foreign-born (Pew Research Center, 2013).…”
Section: Qian Lumentioning
confidence: 99%
“…This can be a concerning assumption as the majority of Black lesbians and women who have sex with women have had sex with a male partner at some point in their life [29][30][31][32]. In addition, Black lesbians and women who have sex with women may be less likely than heterosexual women and women with only male sexual partners, respectively, to have received contraception due to perceptions made by their healthcare provider due to their sexual orientation [33,34] and less likely to be screened for STIs and HIV [35].…”
Section: Critiquementioning
confidence: 99%